Theoretical study of the magnetic properties and the magnetocaloric effect in lanthanum manganite lacunar compounds - Henchiri, C.; Omari, L.H.; Mnasri, T.; Benali, A.; Dhahri, E.; Valente, M.A. (Journal of alloys and compounds, 2022)
•The La1-xxMnO3 (x = 0.1 and 0.2) compounds was successfully prepared by sol-gel method.•The variation of (M) vs. (T) reveals a ferromagnetic to paramagnetic phase transition around TC.•A concordance with the experimental results is noted. Based on the Monte Carlo method and using the Ising model, the magnetic as well as the magnetocaloric properties of lacunar compounds La1-xxMnO3 (x = 0.1 and 0.2) were investigated. Free boundary conditions for our system were applied to simulate the 3D-Ising Hamiltonian of these systems. Cubic magnetic sublattices of size L3, with L = 20, 24 and 28, were investigated in this study to compute the magnetization and the magnetic susceptibility as a function of temperature (T) at various applied fields. In order to calculate the variation of the magnetic entropy versus the applied magnetic field, we have examined an isothermal process by considering a term of magneto-crystalline anisotropy. In order to validate the results, many parameters were calculated. The results obtained are in good agreement with the experimental ones. The high relative cooling power values of our compounds leads to promising material for magnetic refrigeration technology. This material could be considered as a good candidate for applications requiring high values of TC.